Multi-slice computed tomography-assisted endoscopic transsphenoidal surgery for pituitary macroadenoma: a comparison with conventional microscopic transsphenoidal surgery. (November 2015) - Tosaka, Masahiko; Nagaki, Tomohito; Honda, Fumiaki; Takahashi, Katsumasa; Yoshimoto, Yuhei
Abstract : Objectives: Intraoperative computed tomography (iCT) is a reliable method for the detection of residual tumour, but previous single-slice low-resolution computed tomography (CT) without coronal or sagittal reconstructions was not of adequate quality for clinical use. The present study evaluated the results of multi-slice iCT-assisted endoscopic transsphenoidal surgery for pituitary macroadenoma. Methods: This retrospective study included 30 consecutive patients with newly diagnosed or recurrent pituitary macroadenoma with supradiaphragmatic extension who underwent endoscopic transsphenoidal surgery using iCT (eTSS+iCT group), and control 30 consecutive patients who underwent conventional endoscope-assisted transsphenoidal surgery (cTSS group). The tumour volume was calculated by multiplying the tumour area by the slice thickness. Visual acuity and visual field were estimated by the visual impairment score (VIS). Results: The resection extent, (preoperative tumour volume – postoperative residual tumour volume)/preoperative tumour volume, was 98.9% (median) in the eTSS+iCT group and 91.7% in the cTSS group, and had significant difference between the groups ( P  = 0.04). Greater than 95 and >90% removal rates were significantly higher in the eTSS+iCT group than in the cTSS group ( P  = 0.02 and P  = 0.001, respectively). However, improvement in VIS showed no significant difference between the groups. The rate of complications also showed no significant difference. Discussion: Multi-slice iCT-assisted endoscopic transsphenoidal surgery may improve the resection extent of pituitary macroadenoma. Multi-slice iCT may have advantages over intraoperative magnetic resonance imaging in less expensive, short acquisition time, and that special protection against magnetic fields is not needed.